The Andean Representation of Time and Space in the Festival - Urbano, Henrique Osvaldo (1974)
To study the Andean representation of time and space in the festival is to investigate the images, signs and symbols that Andean society produces to define two essential dimensions of its culture. What should we understand by representation? This word is generally used without precise meaning. A set of images grouped around a theme is often thus designated; more specifically, it corresponds to a first attempt to systematize social reality or a part of said reality.